MODEL ALIRAN AIR TANAH UNTUK MEMPREDIKSI PENYEBARAN POLUTAN DI TIMUR CEKUNGAN BANDUNG - Rachmat, Arief; Aji, Ananto (Universitas Negeri Semarang, 2014)
Rancaekek Area, West Java, known as rice granary for years. But, since thetextile industry growing, rice productions are continued to decrease. It waspredicted as the impact of pollutant migration into the farmland. Nowadays,farmland in this area was tend to gone. The potential spread of pollutants can be observed through the direction of groundwater movement. Mass movement ofground water can be seen through the groundwater flow model. This study willprovide an overview of potential spread of pollutants, because it will follow thegroundwater flow. The model is built through data processed with GeographicInformation Systems (GIS). The simulation results of groundwater level isgenerally known that pollutants will move to the south, with local variations tosoutheast and southwest.